Loop-Mediated Isothermal Amplification (LAMP) as a Rapid, Affordable and Effective Tool to Involve Students in Undergraduate Research - Nguyen, Andrew V.; Orlofsky, Amos; Pubill, Kaylynn; Tawde, Mangala; Li, Gaozhen; Mata, Diana; Bermudes, Oscar; Fernandez, Miguel; Santana, Jonathan; Kim, Woochul; Chimbay, Enzon; Kim, Yeeun; et al. (Frontiers in Microbiology, 2020)
Undergraduate research (UR) is a high-impact practice (HIP) to engage undergraduate student in science, technology, engineering and mathematics (STEM), especially from underrepresented groups. UR experiences (UREs) can be integrated into the classroom, making authentic research experiences inclusive and available to all students. However, developing UR pedagogy can be challenging for faculty in resource-limited labs, such as community colleges and small liberal arts colleges. Often molecular biology research methods are expensive, time-consuming and need equipment not readily available or affordable in small schools. Polymerase chain reaction (PCR) is one of the most commonly used techniques in research labs and many UREs. We have investigated loop-mediated isothermal amplification (LAMP) as an inexpensive, accessible alternative to PCR for DNA amplification enabling the identification of microorganisms in the context of UREs. LAMP does not require expensive instrumentation or reagents and uses equipment commonly found in teaching labs. By performing the technique, students learn several key scientific skills that will be useful in their undergraduate or graduate STEM careers. We designed guided independent research experiences for several undergraduates that included the use of LAMP. Students successfully applied the technique to culture samples of common environmental bacteria, including Escherichia coli, Salmonella spp., Staphylococcus aureus, and Enterococcus, and were in addition, able to detect both Salmonella and Enterococcus in directly sampled environmental waters. To highlight the accessibility and affordability of this URE, a simple boiling method was used for DNA preparation from environmental samples. Student response data show positive attitudes toward UR when LAMP is utilized as a research tool to tackle relevant biological questions. The feasibility of using simplified LAMP in UREs points to a potential, more expanded application to public engagement with science and broader and more inclusive interactions with the research community.